Directions of Cultural Transfer in the Grand Duchy of Lithuania: Pochaiv–Vilnius (18th–Early 19th Centuries) - Kažuro, Ina (Lietuvos istorijos studijos, 2025)
The article deals with the issue of cultural relations between Lithuania and Ukraine during the 18th and early 19th centuries on the basis of copies of old books preserved in Vilnius University Library. The object of the study is the Pochaiv Basilian Monastery printing house, one of the largest printing establishments in Ukrainian lands during the 18th century. A total of 152 books produced by the Pochaiv printing house have been identified in Vilnius University Library, of those: 48 books in Cyrillic script (86 copies) and 54 books in Latin script (66 copies). The earliest publication is a 1618-dated theological work by the theologian Kyrylo Tranquillion, which had been printed even before Pochaiv Monastery joined the Church Union. An analysis of the content and provenance of the books from Ukrainian lands reveals not only connections with the realities of the Grand Duchy of Lithuania but also the characteristics of their readers. Pochaiv books in Latin script circulated in the eastern lands of the Grand Duchy of Lithuania, with one even reaching western Lithuania; while most of the Cyrillic books bear the ownership marks of Ukrainian churches. The article includes an Annex presenting a bibliographical list of all Latin-script books from the Pochaiv printing house held in Vilnius university library.